1992
DOI: 10.1152/jappl.1992.72.1.288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abdominal compression on diaphragmatic tendon organ activity

Abstract: Previous studies suggest that afferents in the diaphragm participate in the reflex reduction in phrenic nerve efferent activation when the length of the diaphragm is increased by abdominal compression. The present study determined the response of tendon organ afferents in the diaphragm to increases in abdominal pressure. Five cats were anesthetized with thiopental sodium (60 mg/kg ip to induce, supplemented intravenously). Extracellular recordings from nine individual tendon organ afferents were made from righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Although it is virtually impossible to block selectively the afferent inputs from tendon organs or to stimulate them selectively (Jami, 1992), earlier studies on limb muscles in cats by Lundberg & Winsbury (1960) have shown that afferent volleys from tendon organs in an active muscle can be substantially increased by muscle stretch. Extracellular recordings from cervical dorsal root ganglia in cats by Revelette et al (1992) have also shown increased discharge frequencies from diaphragmatic tendon organs during stretching of the diaphragm by abdominal compression. This procedure, however, would affect a number of additional structures, such as the abdominal muscles, the abdominal viscera, and the large vessels in the abdominal cavity, and the confounding influence of these structures on inspiratory intercostal activity might be difficult to assess.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it is virtually impossible to block selectively the afferent inputs from tendon organs or to stimulate them selectively (Jami, 1992), earlier studies on limb muscles in cats by Lundberg & Winsbury (1960) have shown that afferent volleys from tendon organs in an active muscle can be substantially increased by muscle stretch. Extracellular recordings from cervical dorsal root ganglia in cats by Revelette et al (1992) have also shown increased discharge frequencies from diaphragmatic tendon organs during stretching of the diaphragm by abdominal compression. This procedure, however, would affect a number of additional structures, such as the abdominal muscles, the abdominal viscera, and the large vessels in the abdominal cavity, and the confounding influence of these structures on inspiratory intercostal activity might be difficult to assess.…”
Section: Discussionmentioning
confidence: 97%
“…Although the primary effect of force application may be to elicit increased afferent volleys from tension receptors in the diaphragm (Lundberg & Winsbury, 1960; Revelette et al 1992), the procedure must also reduce or abolish the normal inspiratory shortening of the muscle fibres. Presumably, therefore, muscle spindles were triggered as well.…”
Section: Discussionmentioning
confidence: 99%
“…There is unfortunately very little information about the function of diaphragmatic tendon organs. The available evidence suggests that they may be responsible for relaxation of the diaphragm during an increase in abdominal pressure (Revelette, Reynolds, Brown & Taylor, 1992). The unloading of diaphragmatic tendon organs may, in turn, lead to an increase in phrenic nerve discharges (Jammes, Buchler, Delpierre, Rasidakis, Grimaud & Roussos, 1986;Teitelbaum, Borel, Magder, Traystman & Hussain, 1993).…”
Section: Receptors Unloaded By Contractionmentioning
confidence: 99%
“…Estudos prévios sugerem que aferências diafragmáticas participam da ativação eferente do refl exo de redução do nervo frênico quando o diafragma é alongado pelo aumento da compressão abdominal. Assim, o aumento da atividade diafragmática está associado ao aumento da pressão abdominal [7]. O aumento da pressão diafragmática associado à compressão abdominal está relacionado com o alongamento desse músculo, e produzindo uma contração muscular máxima [8].…”
Section: Introductionunclassified